Increasing Public Accountability to Support Pekanbaru City Community Participation in General Election - Suryandartiwi, Wiwik; Zaky, Abdul (International Journal of Science and Society, 2024)
General elections are the implementation of democracy. However, during the election, there were still allegations of fraud that benefited one of the candidates. This causes election accountability to decrease, which is in line with the decline in public participation. There are several factors that influence the accountability of general elections, such as Attached Supervision, Functional Supervision and Principles of Public Accountability. Research goal is to elaborate the impact of Attached Supervision, Functional Supervision and Principles of Public Accountability on General Election Accountability. The research type is quantitative. The research was conducted on 100 participants in the 2024 Election in Pekanbaru. The sampling technique used the Slovin method to obtain a sample size of 80 respondents. Data collection through questionnaires with SEM PLS for analysis. Research proves that Attached Supervision, Functional Supervision and the Principles of Public Accountability have a significant positive effect on General Election Accountability.